Cannibalism and interspecific predation in a phytoseiid predator guild from cassava fields in Africa: evidence from the laboratory - (:unkn) unknown (My University, 2005)
Interspecific predation and cannibalism are common types of interaction in phytoseiid predator guilds, but the extent and nature of these interactions have not been determined yet in phytoseiid guilds composed of African native and neotropical exotic phytoseiid predators found in cassava habitat in southern Africa. We determined in laboratory experiments the level of cannibalism and interspecific predation among the three phytoseiid mite species Euseius fustis, Iphiseius degenerans, and Typhlodromalus aripo in the absence of food and in the presence of limited or abundant quantities of two food types – Mononychellus tanajoa and maize pollen – commonly found on cassava in Africa. When confined without food, only two T. aripo females laid each two eggs within 5 days, and this species survived longer than I. degenerans and E. fustis. In the presence of con- or hetero-specific larvae or protonymphs, the three species fed more on the former than on the latter, and more on hetero-specifics than on con-specifics. Oviposition rates of the three species did not exceed 0.7 egg/female/day on con- and hetero-specific immatures. Typhlodromalus aripo and E. fustis survived longer on con-specific and hetero-specific larvae and on hetero-specific protonymphs than in the absence of any food, while T. aripo survived longer than the two other species on the same diets. Provision of limited quantity of food decreased interspecific predation rate by I. degenerans and T. aripo, but not by E. fustis, and increased oviposition rate and longevity of all three species. Provision of abundant food, however, eliminated cannibalism by all three species and further reduced interspecific predation rates, but their oviposition and longevity remained relatively unchanged compared with limited food provision. Potential consequences of cannibalism and interspecific predation among phytoseiid mites on cassava for the biological control of M. tanajoa are discussed
Keywords: African Research